Dialogue or Narrative? Exploring Tensions between Interpretations of Genesis 38 - Dickman, Nathan Eric (Religions, 2021)
We examine dialectical tensions between "dialogue" and "narrative" as these discourses supplant one another as the fundamental discourse of intelligibility, through juxtaposing two interpretations of Genesis 38 rooted in changing interpretative paradigms. Is dialogue properly understood as a narrative genre, or is narrative the content about which people are in dialogue? Is the divine-human relationship a narrative drama or is it a dialogue between a god and human beings? We work within parameters laid out by the philosophical hermeneutics of Gadamer (primarily representing dialogue) and Ricoeur (primarily representing narrative). On the one hand, a feminist approach can develop Tamar as a courageous hero in impossible circumstances, strategizing to overturn Judah’s patriarchal naïveté. On the other hand, Judah seems to be able to be read as a tragic hero, seeking to save Tamar. These readings challenge one another, where either Tamar’s or Judah’s autonomy is undermined. By putting these interpretations into dialogue, our aim is to show that neither dialogue nor narrative succeeds the other with finality, and that we can achieve a fragile integration of the two (dialogue and narrative) despite their propensity toward polarization.